PENGARUH SIZE, PROFITABILITY, LEVERAGE, CAPITAL INTENSITY DAN KOMISARIS INDEPENDEN TERHADAP EFFECTIVE TAX RATE PADA PERUSAHAAN MANUFAKTUR DI INDONESIA TAHUN 2016-2019 - Fasifah Hanim; Suyatmin Waskito Adi (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study to analyze the effect of size, profitability, leverage, capital intensity and independent commissioners on the effective tax rate of manufacturing companies in Indonesia (empirical studies on mining, utility, transportation and infrastructure companies listed on the Indonesia Stock Exchange 2016-2019). The population in this study were 128 mining, utility, transportation and infrastructure companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The sampling method uses a purposive sample based on certain criteria. The results of this study indicate that the size of the company has a significant effect on the effective tax rate. Meanwhile, leverage, profitability, capital intensity ratio and independent commissioners have no significant effect on the effective tax rate. Adjusted R Square shows a value of 0,109. This means that 10,90% of the change in the effective tax rate is caused by existing variables. The small coefficient of determination in this study is caused by the independent variable being tested that has little relationship with the dependent variable.